A new signal energy-based approach to acoustic source localization in orthotropic plates: A numerical study. (15th May 2022) - Sen, Novonil; Kundu, Tribikram
Abstract: A new easy-to-implement approach based on the energy of recorded signals is proposed to estimate the acoustic source location in orthotropic plates. The proposed approach (a) requires no time-of-arrival or time-difference-of-arrival estimates, (b) is free from the implicit assumption of the propagation of elastic wave energy along a linear path from an acoustic source to a sensor despite the material anisotropy and (c) can be applied without requiring any direct information on the mechanical properties of the plate material. It is demonstrated that a function of the signal energy at a sensor installed on an orthotropic plate can be modeled as a three-parameter function of the distance of the sensor from the source and its angular position with respect to the source. Considering the source coordinates and the three parameters as unknowns, this model leads to a nonlinear equation involving five unknowns. Considering several sensors, this results in a system of simultaneous nonlinear equations to be solved in the least squares sense by minimizing an objective function of five design variables to obtain an optimum source location estimate. Numerical validations of the proposed approach are performed via four numerical examples with varying plate boundary conditions and excitation pulses, as well as via another numerical example with a Gaussian noise (with a high enough signal-to-noise ratio) added artificially to the signals of one of the above examples. These illustrations reveal that in general the methodology yields sufficiently accurate estimates of the source location.